1993
DOI: 10.1523/jneurosci.13-01-00115.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cell interactions during the migration of an identified commissural growth cone in the embryonic grasshopper

Abstract: One of the fascicles of the posterior commissure of the embryonic grasshopper is pioneered by an individually identifiable neuron named Q1. Q1 initially grows along a longitudinal pathway established by another pioneer neuron, MP1, and then crosses to the midline, where it meets and fasciculates with the axon of the contralateral Q1. The Q1 growth cone follows the contralateral Q1 axon to the contralateral longitudinal pathway, where it then fasciculates with axons of the MP1/dMP2 fascicle. In this work, we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…This idea is supported further by the finding that the cell bodies of Robo3-negative ipsilaterally projecting neurons migrate aberrantly through loss of the commissural neuron-specific receptor Robo3. There is good evidence to support the idea that in some contexts pioneer axons provide a growth substrate for newly migrating axons and cell bodies [10][11][12] . In addition, there are a number of reports of neuronal cell bodies that have the morphological appearance of migrating along axonal tracts 13,14,29,43,44 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This idea is supported further by the finding that the cell bodies of Robo3-negative ipsilaterally projecting neurons migrate aberrantly through loss of the commissural neuron-specific receptor Robo3. There is good evidence to support the idea that in some contexts pioneer axons provide a growth substrate for newly migrating axons and cell bodies [10][11][12] . In addition, there are a number of reports of neuronal cell bodies that have the morphological appearance of migrating along axonal tracts 13,14,29,43,44 .…”
Section: Discussionmentioning
confidence: 98%
“…A small number of studies have shown that the position of cell bodies influence the guidance of axons by the production of chemotactic cues [7][8][9] . Conversely, there is also evidence to support the idea that pioneer axons provide a growth substrate for newly migrating axons and cell bodies [10][11][12] . In addition, during a form of tangential migration, photographic evidence suggests that the migrating neuronal cell bodies appear as if they are using axons as migration scaffolds 5,6,[13][14][15] .…”
mentioning
confidence: 99%
“…Developing axons use adhesive cell contacts between the growth cone and cell adhesion molecules mediating interactions between the cell surface and extracellular matrix molecules. 20 Laminin acts as a cell adhesion molecule and also provides chemotropism by binding chemical factors such as nerve growth factor to the substrate surface, orienting neurite outgrowth. By combining laminin as a chemical cue with the patterned substrates for physical guidance, disruption in alignment due to interactions between cells on microgrooved substrates presenting only physical cues were found to be overcome to a great extent.…”
Section: Discussionmentioning
confidence: 99%
“…Fasciculation of axons enables the younger axons of a given population within the same trajectory to add onto the tracts laid down by pioneer and older axons. During midline crossing in the fly CNS, homotypic axons from opposite sides of the neuraxis meet and grow along each other's surfaces, an interaction that is required for midline crossing (Myers and Bastiani 1993). Reordering of axon subpopulations can occur along pathways through changes in fasciculation, such as when retinal ganglion cell axons from nasotemporal and dorso-ventral retinal quadrants shift their relative positions as they the extend through the optic chiasm (Chan and Chung 1999) and when bundles of retinal axons shift positions as they extend in the optic tract (Walsh and Guillery 1985).…”
Section: Substrata In Vivomentioning
confidence: 99%